Research on Sequence Construction and Characteristics Diagnosis of Droughts and Floods in the Qinling Mountains of China From 1850 to 1959 - Zhang, Shanhong; Qi, Guizeng; Su, Kai; Zhou, Linyan; Bai, Hongying (Frontiers in Earth Science, 2022)
In recent years, under the background of the global climate, drought and flood disasters have occurred frequently in China. Historical climate research is an important part of the international Climate Variability and Predictability project. Based on the existing historical documents and literatures about counties and distributions in the Qinling Mountains from 1850 to 1959, we reconstructed a sequence of drought and flood grades. The characteristics of droughts and floods, including their phases, periodicity, and mutability in all regions from 1850 to 1959, were analyzed by employing the accumulative anomaly, wavelet analysis, and sliding t-test techniques. The results showed that there were 76 droughts and floods in the Qinling Mountains from 1850 to 1959, with droughts and floods occurred 29 and 47 times, respectively, accounting for 38.16% and 61.84% of the total events, respectively. The changes in drought and flood grade sequences in the Qinling Mountains had obvious phases, showing alternating dry and wet periods. A fluctuating climatic phase with both floods and droughts occurred from 1850 to 1879 and from 1949 to 1959; the climate was relatively wet from 1880 to 1912; the climate was relatively dry from 1913 to 1948. The seasonal variation in droughts in the Qinling mountains was concentrated on spring, summer, and back-to-back summer and autumn seasons; while the seasonal variation in floods was concentrated on summer and autumn, and back-to-back summer and autumn seasons. Moreover, there were two periods, 5∼7 a and 11 a, that corresponded to the El Niño-Southern Oscillation (ENSO) activity cycle and were consistent with global climate change. Through the sliding t-test technique and comparison of the drought-flood change sequence, there were two common significant mutations on a decade scale and 20-year scale. The positive PSDI swings are conducive to increased flood occurrence and negative PSDI values to increased drought occurrence, and these changes have good consistency of changes in the two data sources, and also verify the good reliability of the reconstruction results in this paper.